Microstructural Analysis of Strain Rate Dependence for Commercial Dual Phase Steel DP590 Undergoing Finite Strain Deformation - Kamarulzaman, Muhammad Faredzuan; Mohd Nor, Mohd Khir; Abdul Samad, Mohd Syazwan (International Journal of Integrated Engineering, 2021)
This paper analyses the correlation of strain rate dependency of the material with sheet metals manufactured orientation that would influenced the microstructural changes in terms of martensite-ferrite and voids characteristics. The investigation on the deformation behaviour of Advanced High Strength Steel (AHSS) DP 590 was conducted using a uniaxial tensile test along the two principal directions that is through longitudinal (0Â°) and transverse (90Â°) through the strain rates of 1x10-1s-1 to 1x10-4s-1. This allows for a strain rate dependency analysis conducted via stress-strain curve development. Scanning Electron Microscope (SEM) is used to examine the deformed microstructure for micro structural behaviour and for the void analysis on the number of voids and the average void sizes. Referring to the stress-strain curve, it is shown that the mechanical properties of the specimen behaved differently at those preferred orientations and are sensitive to the changes in the loading conditions. This could be observed as the DP590 at 0â° of rolling direction have higher stiffness value as compared to the 90Â° of transverse direction, the variant of the response of the material could be observed to be mildly anisotropically inclined instead of behaves as an isotropically behaved material. The response is also observable within the deformed microstructure. For instance, the higher strain rate indicates a higher number of voids, with a larger average void sizes, from this response it is observed the changes of the strain rate of the material would affect the material behaviour. As for the ferrite-martensite analysis, it could be observed in both different material orientations that as the lower strain rate was applied to the specimen, the strength of the material tends to become weaker since the martensite island becomes smaller at smaller strain rate levels.